Toward Flow Cytometry Based Platelet Function Diagnostics - van Asten, Ivar; Schutgens, Roger E.G.; Urbanus, Rolf T. (Seminars in Thrombosis and Hemostasis, 2018)
The laboratory diagnostics of (inherited) platelet function disorders mainly comprises aggregation and secretion assays, which may be suitable for diagnosing some specific severe platelet function disorders, but are not reliable enough for diagnosing mild platelet function disorders or disorders associated with low platelet count. Flow cytometric assessment of platelet reactivity will expectedly provide additional value during the diagnostic work-up of platelet function disorders because it only requires a small volume of whole blood and allows the measurement of platelet function in thrombocytopenic samples. Flow cytometry has frequently been used to evaluate platelet function in the research setting, and therefore, these assays will require clinical validation before they can be used as routine diagnostic tools. The main challenge in the validation of innovative platelet function diagnostic tests is the lack of a gold standard test for mild platelet function disorders. This review aims to address the many applications of flow cytometry in the current diagnostic work-up of platelet function testing and to discuss the challenges in introducing new tools for diagnosing platelet function disorders.
Keywords: flow cytometry; blood platelets; blood platelet disorders; platelet function tests